Measurements and predictions of harmful releases of the gathering station over the mountainous terrain - Jiang, Xue; Yang, Hao; Lin, Guanming; Dang, Wenyi; Yu, Anfeng; Zhang, Jiedong; Gu, Meng; Xin, Baoquan (Journal of loss prevention in the process industries, 2021)
Having a risk analysis of harmful releases over mountainous terrains through wind tunnel experiment is a frontier problem in China. In this paper, a straight-flow wind tunnel is applied to simulate the atmospheric boundary layer and research the motion of high-sulfur gas released to atmosphere when accidental releases occur in a gathering station over the mountainous terrain. After an analysis of hourly concentration in the field accident for eight wind directions, experimental results reveal that nearby concentration fields are dominated by wind and far-field concentration distribution is dominated by topography, which leads to complete levels of consequence impact for the personnel risk inside and around the gathering station. Based on CFD techniques, a three-dimensional modelling was established in comparison with the wind tunnel experiment, which suggests that CFD prediction had underestimated the near-field gas concentration and the performance could not precisely match actual risks the gathering station causes to the mountainous terrain, which leads to a modified equation for numerical prediction. Instead of proposing a lower personnel risk evaluation obtained through the use of CFD techniques, the wind tunnel experiment offers a new choice for the consequence impact analysis for the petrochemical industry in China.